Tax Competition for Foreign Direct Investment in ASEAN: Is Corporate Income Tax Harmonization the Solution? - Afrianto, H F (KnE Social Sciences, 2018)
This research is motivated by the global trends that indicate many countries are competing to attract foreign direct investment flows through the adaptation of the tax policies that encourage harmful tax competition issues. The interests of addressing these issues are to minimize the distortion of single market as in EU (European Union) and to ensure efficient tax structure in ASEAN. Adopting quantitative approach, secondary data were obtained through literature review. It was found that the phenomenon of tax competition in ASEAN strengthened as indicated by the higher rate of tariff reduction of corporate income tax in ASEAN, fundamental differences system of taxation in ASEAN and various tax incentives offered. To overcome this problem, the author examines the urgency of the harmonization of income tax in the ASEAN with comparative study with CCCTB (Common Consolidated Corporate Tax Base) in EU. Looking ahead, ASEAN will need the political commitment to start corporate income tax harmonization in ASEAN with regard to neutrality and subsidiarity criteria that could be a solution to overcome the practice of harmful tax competition. Keywords: tax competition, corporate income tax harmonization, foreign direct investment, corporate income tax rate, tax administration